PP.06.33: HYPERTENSION IS AN INDEPENDENT DETERMINANT OF AORTIC ANATOMY. (June 2015) - Rosenbaum, D.; Girerd, X.; Kachenoura, N.; De Cesare, A.; Cluzel, P.; Redheuil, A.
Abstract : Objective: Hypertension and age have been associated with changes in aortic and left ventricle anatomy in general population. Our objectives were to assess determinants of aortic anatomic indices in hypertension using cardiovascular magnetic resonance (CMR). Figure. No caption available. Design and method: Heart and of proximal aorta CMR exam (1.5T Siemens) was performed. Ascending aortic diameters (D) were calculated using the ARTFUN software and an automated segmentation of SSFP cine acquisitions acquired in the axial view, during breath-holding, at the level of pulmonary bifurcation perpendicular to the aorta. Aortic arch (AoA) width (W) defined as the distance between the center of the ascending and descending aorta cross-sections. AoA height (H) defined as the length of the orthogonal projection of the inflection point of the AoA centerline, positioned at the top of the arch, on the width of the aortic arch. AoA length (L) was estimated from SSFP acquisitions as the distance between the ascending and proximal descending aorta locations used for flow measurements. Telediastolic Left Ventricle indexed mass (M) and volumes (V) were semi-automatically calculated using the QMASS ® software on small axis Cine sequences. Central Blood pressures (BP) recorded using SPhygmocor ® just before MRI were used to define BP levels. Results: Population included 80 subjects (mean age 52 ± 13; 53% male): 23 controls and 57 treated hypertensives (28 controlled and 29 uncontrolled). Male proportion was 51%. Demographics were comparable in the 3 groups but age was a slightly younger in controls. M/V differed between the 3 groups (p < .03): 3.8, 3.9 and 4.4 in control subjects, controlled and uncontrolled hypertensives respectively. AoA W, L, H and D differed between control subjects and uncontrolled hypertensives (Figure 1 p < .001). Univariate analysis showed that significant associations of W and M/V with age, central mean BP (cMBP), BMI and gender whereas L and H only correlated to age and gender. Multivariate analysis showed after adjustment for age, gender, BMI, cMBP, independent influence of cMBP, and age on AoW and D as well as with M and M/V ratio. Conclusions: Along with age, hypertension is an independent determinant of aortic anatomy